Control of Male and Female Fertility by the Netrin Axon Guidance Genes - Newquist, Gunnar (Public Library of Science, 2013)
The netrin axon guidance genes have previously been implicated in fertility in C. elegans and in vertebrates. Here we show that adult Drosophila lacking both netrin genes, NetA and NetB, have fertility defects in both sexes together with an inability to fly and reduced viability. NetAB females produce fertilized eggs at a much lower rate than wild type. Oocyte development and ovarian innervation are unaffected in NetAB females, and the reproductive tract appears normal. A small gene, hog, that resides in an intron of NetB does not contribute to the NetAB phenotype. Restoring endogenous NetB expression rescues egg-laying, but additional genetic manipulations, such as restoration of netrin midline expression and inhibition of cell death have no effect on fertility. NetAB males induce reduced egg-laying in wild type females and display mirror movements of their wings during courtship. Measurement of courtship parameters revealed no difference compared to wild type males. Transgenic manipulations failed to rescue male fertility and mirror movements. Additional genetic manipulations, such as removal of the enabled gene, a known suppressor of the NetAB embryonic CNS phenotype, did not improve the behavioral defects. The ability to fly was rescued by inhibition of neuronal cell death and pan-neural NetA expression. Based on our results we hypothesize that the adult fertility defects of NetAB mutants are due to ovulation defects in females and a failure to properly transfer sperm proteins in males, and are likely to involve multiple neural circuits.